Celtis atlantica (Cannabaceae): A new endangered tree species from southwest of Brazil - Zamengo, H. B. (2023)
During the Neotropical review of Celtis, a new species (Celtis atlantica) endemic and endangered to southeastern Brazil was discovered. A morphological description, a distribution map, conservation status, taxonomic notes, illustrations, and an identification key of the Celtis from the Southern Cone and Brazil are provided.